Kedudukuan Hukum Islam Dalam Sistem Hukum Nasional - Saharuddin Saharuddin; Muh. Fadli Faisal Rasyid; Auliah Ambarwati (Jurnal Litigasi Amsir, 2021)
In discussing Islamic Law amid National Law, the focus will be on the position of Islamic Law in the National Law system. This study aims to determine the position of Islamic law in the national legal system. The research method used in this study uses a normative type of research, namely by examining laws and regulations, theories, and concepts related to the problems studied. This research is supported by the approach used in this research, namely the legislative approach, and comparative approach. The results of the study indicate that the contribution of Islamic law is very large in the development and development of National Law, namely that every product of the law made by the Legislative Body is always inspired by Islamic Law. Constraints The main obstacles and problems of Islamic Law in Indonesia are related to the process of integration into National Law.